Cooperativity between individual transporter protomers: new data fuelling old complexes. (15th March 2015) - Sitte, Harald H.; Schütz, Gerhard J.; Freissmuth, Michael
<x xml:space="preserve">Abstract</x> Neurotransmitter transporters are arranged in an oligomeric quaternary structure as evidenced by crosslinking or fluorescence resonance energy transfer (FRET)‐microscopy. In a study by Zhen and colleagues highlighted by this Editorial in the current issue of Journal of Neurochemistry, the combination of mutant and wild‐type dopamine transporter (DAT) has been used to establish the cooperation between transporter protomers; the DAT mutant version has an altered affinity for the radiolabelled inhibitor [3H]CFT. Zhen and colleagues predict how saturation‐binding curves ought to look, if the two binding sites (i.e. of the wild type and the mutant DAT) operated independently. The results are clear‐cut: the experimental observations are inconsistent with curves obtained by mixing independent binding sites. Thus, by definition, the binding sites cooperate. <boxed-text content-type="graphic" id="jnc13086-blkfxd-0001" position="anchor" orientation="portrait"> </boxed-text> Read the full article 'Dopamine transporter oligomerization: impact of combining protomers with differential cocaine analog binding affinities' on page 167.